Fulfilling the college promise: moving from access to completion for second-year promise students at Long Beach City College - Corral, Nohel (Kansas State University, 2019)
This study examined whether a significant relationship existed between participation in the college promise program and student persistence, success, and completions at Long Beach City College (LBCC) through a Completion by Design framework. Participants for this study included college promise program students from cohort years 2013, 2014, and 2015 with a control group identified using propensity score matching. The intent of this study was to identify whether an association existed between participation in the LBCC college promise program and student progress and completion. The results suggested that college promise program students were more likely to persist than non-college promise program students. However, non-college promise program students were more likely to have higher GPAs, more units completed, and complete certificates, degrees, and/or transfer than their college promise program peers. These results suggest that providing students with supports only upon connection with and entry to the college may not be enough to improve long-term student success outcomes.
Keywords: Long Beach City College; College promise; Financial aid; Student persistence; Student completions